DEPRESSION IN DANIELLE STEEL’S NOVEL BIG GIRL - Anggraini, Vira Dhea; Hariani, Safitri (JOURNAL OF LANGUAGE, 2024)
This study explores the protagonist's struggle with depression as portrayed in Danielle Steel's novel, Big Girl. Depression, a prevalent and debilitating mental health condition, profoundly impacts one's emotions, cognition, behavior, and perception of the world. It is not uncommon for individuals to experience multiple episodes of depression throughout their lives, highlighting its chronic and recurrent nature. Given its severity, depression demands serious attention and intervention. Regrettably, many older adults grapple with undiagnosed and untreated depression, often hesitating to seek professional assistance. The analysis presented herein focuses on discerning the root causes and consequential effects of the protagonist's depression. Drawing from the theoretical frameworks proposed by Munthe and Dewi, this study employs a descriptive qualitative methodology. The findings illuminate that the protagonist's depression stems from various sources, including internal struggles, familial dynamics, and societal pressures. Specifically, she grapples with the weight of paternal expectations, a diminished sense of self-worth, unfair comparisons, and societal rejection. Moreover, the novel vividly portrays the adverse impacts of depression, encompassing weight loss, disrupted sleep patterns, feelings of profound emptiness, and even suicidal ideation.